BEM and FEM results of displacements in a poroelastic column - Albers, Bettina; Savidis, Atavros A.; Taşan, Ercan H.; Estorff, Otto von; Gehlken, Malte (Zielona Góra: Uniwersytet Zielonogórski)
The dynamical investigation of two-component poroelastic media is important for practical applications. Analytic solution methods are often not available since they are too complicated for the complex governing sets of equations. For this reason, often some existing numerical methods are used.
Keywords: Finite Element Method (FEM); boundary element method (BEM); poroelastic media